'Millionella massiliensis' gen. nov., sp. nov., a new bacterial species isolated from human right colon. (May 2017) - Mailhe, M.; Ricaboni, D.; Benezech, A.; Cadoret, F.; Fournier, P.-E.; Raoult, D.
Abstract: We report here the main characteristics of 'Millionella massiliensis' strain Marseille-P3215 T (= CSUR P3215), which was isolated from a human right colon liquid sample.